MINIMIZING RENOVATION PROJECT DELAYS(CASE STUDY: PT PERTAMINA RETAIL) - Khaerunnisa, Soraya
PT Pertamina Retail is a PT Pertamina Niaga subsidiary which has responsible for operating COCO gas stations owned by PT Pertamina (Persero). Currently, PT Pertamina's competitors are increasingly developing their business and increasing their outlets, which will become a challenge for PT Pertamina Retail. So, PT Pertamina Retail is constantly upgrading and improving the appearance of fuel station facilities, ensuring that the facilities has an optimal function. This is also stated in the company's strategy and listed in the 5R program (Ringkas (Brief), Rapi (Neat), Resik (Clean), Rawat (Caring), Rajin (Diligent)).